Gastrointestinal Complaints During Exercise: Prevalence, Etiology, and Nutritional Recommendations - Oliveira, Erick Prado de; Burini, Roberto Carlos [UNESP]; Jeukendrup, Asker (Adis Int Ltd, 2014)
Gastrointestinal problems are common, especially in endurance athletes, and often impair performance or subsequent recovery. Generally, studies suggest that 30-50 % of athletes experience such complaints. Most gastrointestinal symptoms during exercise are mild and of no risk to health, but hemorrhagic gastritis, hematochezia, and ischemic bowel can present serious medical challenges. Three main causes of gastrointestinal symptoms have been identified, and these are either physiological, mechanical, or nutritional in nature. During intense exercise, and especially when hypohydrated, mesenteric blood flow is reduced; this is believed to be one of the main contributors to the development of gastrointestinal symptoms. Reduced splanchnic perfusion could result in compromised gut permeability in athletes. However, although evidence exists that this might occur, this has not yet been definitively linked to the prevalence of gastrointestinal symptoms. Nutritional training and appropriate nutrition choices can reduce the risk of gastrointestinal discomfort during exercise by ensuring rapid gastric emptying and the absorption of water and nutrients, and by maintaining adequate perfusion of the splanchnic vasculature. A number of nutritional manipulations have been proposed to minimize gastrointestinal symptoms, including the use of multiple transportable carbohydrates, and potentially the use of nutrients that stimulate the production of nitric oxide in the intestine and thereby improve splanchnic perfusion. However, at this stage, evidence for beneficial effects of such interventions is lacking, and more research needs to be conducted to obtain a better understanding of the etiology of the problems and to improve the recommendations to athletes.